(untitled) (Pulse, 2016)
A 41 year old nondiabetic, non hypertensive male was admitted in AHD through neurosurgery OPD with the complaints of left eye watering and left sided weakness for 1 month. MRI examination revealed a mass / lesion in the left prepontine cistern, left CP angle with extension to left middle cranial fossa which was histologically found to be chondroma, an extremely rare tumour in the above mentioned location. Pulse Vol.8 January-December 2015 p.81-84